2003
DOI: 10.1097/01.blo.0000057791.10364.7c
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Pelvis After Resection of Tumors About the Acetabulum

Abstract: Periacetabular resections for primary malignancies and metastatic disease require reconstruction to restore weightbearing along anatomic axes. Without reconstruction, patients are unable to ambulate independently, and are left with a disfigured pelvis and shortened limb. The current authors describe a reconstruction technique using Steinmann pins augmented with methylmethacrylate reconstruction, and autoclaved autografting, in combination with total hip arthroplasty, after resection of primary sarcomas of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 16 publications
0
59
0
2
Order By: Relevance
“…Numerous reconstruction methods and kinds of differently designed endoprostheses after pelvic tumour resection have been reported (Table 3). Satcher et al [34] reported 15 patients received a reconstruction method of autoclaved autograft and attained a 60% survival rate at five years. Aljassir et al [5] reported 27 cases reconstructed with saddle prostheses and 59% survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reconstruction methods and kinds of differently designed endoprostheses after pelvic tumour resection have been reported (Table 3). Satcher et al [34] reported 15 patients received a reconstruction method of autoclaved autograft and attained a 60% survival rate at five years. Aljassir et al [5] reported 27 cases reconstructed with saddle prostheses and 59% survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…In one report [13] of 28 patients with internal hemipelvectomy and prosthetic reconstruction of pelvic tumours, the average blood loss was 4,793 ml (range: 1,500-12,000 ml). In another study [22], the blood loss of 15 procedures of tumour resection about the acetabulum ranged between 500 and 35,000 ml. A wide variety of risk factors influence perioperative blood volume loss.…”
Section: Introductionmentioning
confidence: 99%
“…Extirpation of tumor tissue is expected to cause some degree of functional impairment; therefore, efforts should be made to decrease such impairment. Studies have reported on the functional outcomes of impairments on musculoskeletal tumor treatment [9,10,14,16,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this system has been used in numerous studies to evaluate functional outcomes [9,10,14,16,17,19,22], making it one of the most widely used functional evaluation tools. The original scoring system was written in English and subsequently has been translated into Brazilian Portuguese and Japanese.…”
Section: Introductionmentioning
confidence: 99%